Citation analysis of journal of natural rubber research, 1988-1997 - Tiew, W.S.; Kaur, Kiran (Faculty of Computer Science and Information Technology, University of Malaya, 2000)
An analysis was carried out on 4181 citations appended to the References Section of 250 research articles and 8 short communications in Journal of Natural Rubber Research. It was found that journals/serial publications were the most cited source of information among rubber scientists (72.4). The study also revealed the trend towards collaborative research among rubber scientists as two or more authors authored 61.56 of rubber literature. Rubber scientists are also quite up-to-date in their search for knowledge, as references cited were fairly recent with 55.97 covering the period of 1978-1997. The study also found that Rubber Chemistry and Technology toped the list (6.60) as the most cited serial publication in the field of rubber research.